Effect of thermal and ultraviolet treatments on the stability of antioxidant compounds in single strength pineapple juice throughout refrigerated storage - Goh, Sur Guat; Mohd Adzahan, Noranizan; Leong, C. M.; Sew, Chang Chew; Sobhi, Babak (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Thermal treatment is commonly applied in juice manufacturing as a method to pasteurize juices. However the heat may deteriorate some of the essential compounds in the juice, especially heat-sensitive antioxidants. Therefore non-thermal treatment such as ultraviolet (UV) ray has been proposed as an alternative for pasteurization. The objective of this study was to compare the effect of thermal and UV treatments on the content of antioxidants (phenolic acids, flavonoids, carotenoids, ascorbic acids) and antioxidant capacity of single strength pineapple juice. The antioxidants stability of juices throughout 14 days of refrigerated storage was also studied. Ultraviolet treatment shows higher ascorbic acid content after treatment as compared to thermally treated single strength pineapple juice. Storage time affected the studied antioxidants, where UV treatment provided better stability to ascorbic acid content while thermal treatment provided better stability to flavonoids and carotenoids.